Development of PBL-Based Learning Media Using Smart Apps Creator to Improve Science Learning Outcomes for Grade IV Elementary School Students - Nanda Gustie Wulandari; Desi Wulandari (Postgraduate, University of Mataram, 2025)
Low student learning outcomes are influenced by the use of new learning models and media that are still not ideal for science and the science learning process. Given that these challenges require the development and evaluation of learning media that aim to improve the educational achievements of children in grade four, this study aims to do so. The maker of smart applications based on PBL (Problem Based Learning) content about the Form of Matter and Its Changes is the learning media that is developed. Research and development, or RnD, is the process used, with the ADDIE model as the development framework. Participants in this study numbered 27 people from grade IV of SD Negeri 1 Brobot. Both pre- and post-test methods, as well as non-test methods such as observation, interviews, questionnaires, and documentation, were used in the data collection process. The media validator reached a very feasible level of 93.3% and the material validator 87%. A significant difference (Sig. 0.00 <0.05) was shown by the t-test between the pretest and posttest data. The N-gain test shows moderate requirements, with a small scales value of 0.61 and a large scales value of 0.64. Based on these findings, it is reasonable to conclude that the developer of PBL-based application learning media has created practical and effective substance-based content to be used in improving the educational outcomes of fourth grade students of SD Negeri 1 Brobot.